1985
DOI: 10.1007/bf00905727
|View full text |Cite
|
Sign up to set email alerts
|

Parental separation/divorce and adolescents: An examination of factors mediating adaptation

Abstract: This study examined the relationship between differences in current adjustment as they related to a number of demographic, personal, and situational factors for 65 late adolescents/young adults who had experienced this life transition. Utilizing multiple regression analyses, several factors emerged as particularly salient mediators of the adolescents' postdivorce adjustment, including distance from home, coping style, family cohesion, conflict and organization, and the use of family members for support. The im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…Specifically, adolescents may be less likely to blame themselves for the occurrence of the interparental conflict (Farber et al 1985). In claiming less responsibility, adolescents demonstrate less maladjustment, as suggested by current and previous findings (Dadds et al 1999).…”
Section: Discussionmentioning
confidence: 70%
“…Specifically, adolescents may be less likely to blame themselves for the occurrence of the interparental conflict (Farber et al 1985). In claiming less responsibility, adolescents demonstrate less maladjustment, as suggested by current and previous findings (Dadds et al 1999).…”
Section: Discussionmentioning
confidence: 70%
“…Several investigations have also reported that social competence Long, Forehand, Fauber, & Brody, 1987), cognitive competence Wierson et al, 1988), and grade point average (GPA; Wierson et al, 1988) are related to marital conflict. Several studies have also found relationships between children's perceptions of family conflict and negative child outcomes (e.g., Enos & Handal, 1986;Farber, Felner & Primavera, 1985;Slater & Haber, 1984), but only studies that assess marital conflict are considered in the present article. Table 1 presents a summary of studies that examine the relationship between marital conflict and children's adjustment.…”
Section: Dimensions Of Conflict)mentioning
confidence: 99%
“…Findings from studies of the relationship of coping strategies and various outcomes in adolescents with divorced and married parents also have been inconsistent (Farber, Felner, & Primavera, 1985;Kurdek, Blisk, & Siesky, 1981;Torestad, Magnusson, & Olah, 1990). Among the coping behaviors related to measures of distress and psychological well-being were emotional distancing, interpersonal reasoning, seeking support, the use of denial, and blaming.…”
mentioning
confidence: 99%